Pakistan’s Domestic Political Dynamics and Need for Civil Military Cooperation - Babbar, Muhammad Asgher; Pervaiz, Aslam; Baloch, Ali Jamshed (Annals of Human and Social Sciences, 2025)
Since its independence on August 14, 1947, the country’s focus remained on strengthening single institution (military). Hence the remaining two institutions, such as; executive and judiciary; which are considered equally important in the smooth running of state remained weak. Eventually, leading to single institution emerging as the most powerful, thus the relationship between executive and military has remained strand. This study focuses on the relationship between civilian and military institutions. The study undertakes to explore the strong and weak positions of both institutions and possibilities of cooperation between them. Apart from that which political party can be most acceptable option for military institution to work with to strengthen the nation and national security? To analyze the situation, this research applied qualitative method. The findings suggest that the regional and international situation demands greater cooperation among two institutions to ensure security and survival of the country.